Homosexual Live-in relationship in India: Socio Legal Dimension in reference to Right to life or Social stigma - Mathur, Vaishali (International Journal of Psychosocial Rehabilitation, 2020)
Live-in relationship is a long-lasting oratory issue for last one decade, but the law related to live- in relationship in India concern to LGBT (lesbian, gay, bisexual, transgender) not clear and apposite yet. In Indira Sharma vs V.K.V Sharma2, Honorable Supreme Court gave an innovative and milestone decision by describing five kinds of live-in relationship in India. The fifth one is about homosexual live-in relationship in India. The researcher seek to elucidate in this article that to legalize the homosexual live-in relationship in India surge the societal censure, threatens and demoralize the traditional marriage concept, In contradiction of natural progression, Standardization of immorality and peculiarity, No procreation of children that assimilates gay and lesbian in this heterosexual society, Increase the unusual and non-traditional marriages and relationship- polygamy, bigamy, bestiality, incest and more, Boost the Homosexual relation in society that is against the natural cohabitation of men and women, Inharmoniousness of many religions to belief such immoral kind of relationship. The article also tries to put light on some grey and undiscussed issue of homosexual cohabitation that adoption right, succession right, maintenance right, protection of Domestic Violence Act 2005 sec 2(f) executed or not on homosexual live-in relationship. In writing this article, the author no intention to denigrate or criticize any individual. In cerebrally contrasting individuals or administrations endorsing the homosexual live-in relationship, the author’s only intention is the resistance and protection of traditional marriage institution, the family harmony, and the precious, valuable assortments of Indian traditional culture.